(3GdJCSjS GdGFJeGfj dYde GdebGUO (B/s - (3YHO GdQMef, Wgs 1944- ((3HjQhJ (B- (3dHfGf (B:s (3eQcR fghV ddOQGSGJ hGdHMhK,s, 2022)
(3HYO cJGH (B"(3GdeaGgje GdCNdGbjI Hjf GdGFJeGfjI hGdYdeGfjI(B" (3GdPj hVY ajg GdajdSha GdeZQHj GdeYQha Wg YHO GdQMef CUhnd fXQjJg aj GdCNdGb GdGFJeGfjI, gG gh aj gPG GdcJGH GdPj Hjf jOjc(B- (3jbhe HJWHjb gPg GdfXQjI aj eLGd (B"(3Yde GdebGUO(B". (3EP jQi Cf gPG GdYde jfHfj Ydi eHOC GOYGA GdGNJUGU HGdHJ aj ebGUO GdTGQY ; aYfOeG jbhd GdebGUOj(B: "(3gPG eQGO GdTGQY ef Mceg(B"(3, aEfg dG jOYj eYQaI Mce GdTGQY aMSH, Hd jOYj CjVG GdMce Ydi Mceg, eeG jLYd GdebGUOj dG YGdeG aMSH, Hd MGceG CjVG; hEPG cGfJ eYQaJg HGdMce GdTQYj JLYd Ydeg jMUd (B"(3GdTQYjI(B"(3, aEf Mceg Ydi GdMce GdTQYj(B.s
(3HHdjhLQGajI (B: (3UaMI (B508-512.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3ebGUO TQjYIs -- (3adSaI ESdGejIs; (3GdadSaI GdESdGejIs